2020
DOI: 10.1016/j.jhazmat.2019.121059
|View full text |Cite
|
Sign up to set email alerts
|

Superior performance of FeVO4@CeO2 uniform core-shell nanostructures in heterogeneous Fenton-sonophotocatalytic degradation of 4-nitrophenol

Abstract: Porous FeVO4 nanorods decorated on CeO2 nanocubes (FeVO4@CeO2) were successfully prepared via a facile hydrothermal route and tested in the degradation of 4-nitrophenol (4-NP) for enhanced heterogeneous oxidation using ultrasonic (US), ultraviolet (UV), and binary irradiation US/UV, respectively. The nanostructure of the core-shell FeVO4@CeO2 was characterised using XRD, SEM, EDS elemental mapping, TEM, HRTEM, SAED, FTIR, Raman, BET, point of zero charge (PZC), XPS analysis and UV-vis DRS. The effect of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 80 publications
1
22
0
1
Order By: Relevance
“…The comparison of catalytic dosage, sonication time and removal efficiency of proposed catalyst and reported catalysts for the degradation of nitrophenol compounds was presented in Table 1. As can be seen, the proposed catalyst displayed relatively short sonication time and also considerable removal efficiency comparing with other reported catalysts [22][23][24]45,46]. The results reported in this study showed that the prepared catalyst is a potential candidate for the removal of PNP from aqueous solution.…”
Section: Comparison With Other Reported Heterogeneous Sono-fenton Catalystssupporting
confidence: 51%
“…The comparison of catalytic dosage, sonication time and removal efficiency of proposed catalyst and reported catalysts for the degradation of nitrophenol compounds was presented in Table 1. As can be seen, the proposed catalyst displayed relatively short sonication time and also considerable removal efficiency comparing with other reported catalysts [22][23][24]45,46]. The results reported in this study showed that the prepared catalyst is a potential candidate for the removal of PNP from aqueous solution.…”
Section: Comparison With Other Reported Heterogeneous Sono-fenton Catalystssupporting
confidence: 51%
“…40 Meanwhile, for the FVO, the humps observed at 645 cm À1 and 320-200 cm À1 were ascribed to the stretching vibration of F-O and non-equivalent Fe-O bonds, 41,42 respectively, while the bands located at 500-350 cm À1 can be assigned to the vibration of the V-O-V bonds. 43 From the Raman spectra of FVO 40 -MS, the vibrations of two S atoms with respect to Mo (E 1 2g ) were red-shifted from MS 383.3 cm À1 to 378.5 cm À1 owing to the built-in lattice strain changes occurring at the E 1 2g peak position, which could be attributed to the rippled morphology of the MoS 2 crystal with the existence of FeV 3 O 8 . 44 It was noted that the 338 cm À1 peak was assigned to the S-Fe bond in the E g mode.…”
Section: Characterization Of the Catalystsmentioning
confidence: 98%
“…Nano-pyrite is dissolved to release Fe 2+ under acidic conditions, and then H 2 O 2 is added. H 2 O 2 produces a large amount of •OH under the action of Fe 2+ , and nally •OH catalyzes reduction of p-nitrophenol to produce CO 2 and H 2 O. Eshaq [13] et al prepared a core-shell nanostructure FeVO 4 @CeO 2 , which was used as a catalyst to achieve the catalytic reduction and degradation of p-nitrophenol. Catalytic hydrogenation is a method in which NaBH 4 , H 2 O or C 2 H 5 OH is used as a hydrogen donor to provide active hydrogen for the catalytic process, and then the aromatic nitro compound is catalytically reduced to an aromatic amino compound [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%